IAR signatures in the ionosphere: Modeling and observations at the Chibis-M microsatellite. (February 2017) - Pilipenko, V.; Dudkin, D.; Fedorov, E.; Korepanov, V.; Klimov, S.
Abstract: A peculiar feature of geomagnetic variations at middle/low latitudes in the ULF band, just below the fundamental tone of the Schumann resonance, is the occurrence of a multi-band spectral resonant structure, observed by high-sensitivity induction magnetometers during nighttime. The occurrence of such spectral structure was commonly attributed to the Ionospheric Alfvén Resonator (IAR) in the upper ionosphere. Rather surprisingly, while ground observations of the IAR are ubiquitous, there are practically no reports on the IAR signatures from space missions. According to the new paradigm, the multi-band spectral structure excited by a lightning discharge is in fact produced by a regular sequence of an original pulse from a stroke and echo-pulses reflected from the IAR upper boundary. Upon the interaction of initial lightning-generated pulse with the anisotropic lower ionosphere, it partially penetrates into the ionosphere, travels up the ionosphere as an Alfvén pulse, and reflects back from the upper IAR boundary. The superposition of the initial pulse and echo-pulses produces spectra with multiple spectral peaks. Our modeling of Alfvénic pulse propagation in a system with the altitude profile of Alfven velocity modeling the realistic ionosphere has shown that IAR spectral signatures are to be evident only on the ground and above the IAR. Inside the IAR, the superposition of upward and downward propagating pulses produces a more complicated spectral pattern and the IAR spectral signatures deteriorate. We have used electric field data from the low-orbit Chibis-M microsatellite to search for IAR signatures in the ionosphere. We found evidence that the multi-band structure revealed by spectral analysis in the frequency range of interest is indeed the result of a sequence of lightning-produced pulses. According to the proposed conception it seems possible to comprehend why the IAR signatures are less evident in the ionosphere than on the ground. Highlights: IAR signatures are produced by sequence of pulses reflected from topside ionosphere. Superposition of initial and echo-pulses makes IAR signatures in space less evident than on the ground. Microsatellite observations confirmed that rare IAR signatures in the upper ionosphere are result of sequence of lightning-produced impulses.